Comparative analysis of inductively coupled plasma mass spectrometry and alpha spectrometry methods to measure plutonium activity in biosubstrates - V. R. Batalov; M. V. Ishunina; A. V. Efimov; A. B. Sokolova (Радиационная гигиена)
Currently, the most common methods to measure the activity of transuranium elements in biological samples are alpha radiometry and alpha spectrometry. Of these, alpha spectrometry is the most sensitive and selective method. However, this method is not sufficiently sensitive to control hardly soluble compounds of plutonium in the human body. For example, upon an intake of hardly soluble compounds of plutonium at the level of annual limit of intake, a year later, Pu in a daily urine sample is expected to be 0.4 mBq. Since the lower limit of measurement of alpha spectrometry is about 0.5 mBq, during the first 2 years as minimum, the workers who have contact with hardly soluble compounds of plutonium are not provided with a reliable monitoring of intakes. To solve this problem, a new technique of analysis was developed based on the plutonium activity measurement using the method of inductively coupled plasma mass spectrometry. This technique allows measuring plutonium by mass spectrometer in daily urine samples and blood samples after separation from interfering isotopes by anionic exchange chromatography. The method takes much less measurement time and is much more sensitive to long-lived isotopes. It enables reducing the lower limit of measurement by a factor of five compared to the alpha spectrometry method. Also, the technique for the first time allows to measure separately the activity of plutonium-239 isotopes and plutonium-240 isotopes, the energies of which are indistinguishable on alpha spectra. The plutonium activity was measured by the two methods in parallel in 88 daily urine samples collected from the personnel of the federal state unitary enterprise “Mayak Production Association” working primarily with hardly soluble compounds of plutonium. The analysis of the measurements of these samples demonstrated no statistically significant differences between the results obtained. Also, these results testify to better applicability of mass spectrometry for the activities below the lower limit of measurement of alpha spectrometry. The developed method of analysis can be applied to estimate the levels of current intake of hardly soluble compounds of plutonium, for retrospective dosimetry and as an express method to obtain the intake estimates by the plutonium activity in blood in non-routine situations.